Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

This is a really simple problem but I am unsure if I have proved it properly.

By contradiction:

Suppose that $x \geq 1$ and $x< \sqrt{x}$. Then $x\cdot x \geq x \cdot 1$ and $x^2 < x$ (squaring both sides), which is a contradiction.

share|improve this question
    
I think you're only missing a note that $x\cdot x\ge x\cdot 1\to x^2\ge x$ contradicts the squaring of $x^2\lt (\sqrt x)^2\to x^2\lt x$... –  abiessu Jan 29 at 20:15
    
So you're saying that it would be better to write out that step? Ok –  grayQuant Jan 29 at 20:17
    
Yes; note that $x^2\gt 1$ does not necessarily contradict $x^2\lt x$, and is not necessarily guaranteed by the given conditions. –  abiessu Jan 29 at 20:18
    
The first time I squared both expressions, I changed it to $ x\cdot x$ for the first one then squaring the second. Now I have a valid proof? –  grayQuant Jan 29 at 20:21
    
Close, just one more note that you extend $x\ge 1$ to $x^2\gt x$ (note the change from "greater than or equal" to "greater than") which is not necessarily true. –  abiessu Jan 29 at 20:24

3 Answers 3

Here is a direct proof (without contradiction)

$x=1+r$ with $r\geq0$ . Then $x^2=(1+r)^2=1+2r+r^2\geq1+r=x\rightarrow x^2\geq x\rightarrow x\geq\sqrt x$

share|improve this answer
    
Nice thanks, just curious did you have a reference for this or just solved it. I would like to look at the reference if you used any –  grayQuant Jan 29 at 20:23
3  
Sorry, I don't have a refference, I just happened to think about this in the shower the other day. but transforming the variable can be useful sometimes. –  Jorge Fernández Jan 29 at 20:25
    
This is a neat way to do it. I've found that I sometimes rely on contradiction too much so seeing direct proofs of things I would otherwise use contradiction on is very refreshing. –  Cameron Williams Jan 29 at 21:13

Assume $x \geq 1.$ Then $x - 1 \geq 0$ and $x > 0,$ and hence

$$ x(x-1) \; = \; x^2 - x \; \geq \; 0$$

since the product of two non-nonegative expressions is non-negative.

Factoring $x^2 - x$ as a difference of squares gives

$$ \left(x - \sqrt{x} \right) \left( x + \sqrt{x} \right) \; \geq \; 0$$

Since $x + \sqrt{x}$ is positive (both $x$ and $\sqrt{x}$ are positive), it follows that $x - \sqrt{x}$ is non-negative, which is easily seen to be equivalent to what you wanted to prove.

share|improve this answer
    
Neat :). But, the $0$ answer is neater :D –  Dror Jan 29 at 21:21

As a contra-positive, assuming $x$ is not negative: $$\sqrt{x} > x \implies x>x^2 \land x \neq0 \implies 1>x$$ (1st implication is by squaring (Which is obviously an increasing function here), 2nd implication is by dividing by $x$)

So, equivalently: $$x \geq 1 \implies x \geq\sqrt{x}$$

Alternatively, for a more direct proof, you can rely on $\sqrt{\cdot}$ being an increasing function in $\mathbb R_{\ge 0}$ domain: $$x \geq 1 \implies x^2 \geq x \implies x \geq\sqrt{x}$$ (1st implication is by multiplying by $x$, 2nd implication is by taking the square root, relying on it being increasing)

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.